2018
DOI: 10.1186/s11658-018-0085-1
|View full text |Cite
|
Sign up to set email alerts
|

Mst1 regulates post-infarction cardiac injury through the JNK-Drp1-mitochondrial fission pathway

Abstract: BackgroundPost-infarction cardiac injury is closely associated with cardiac remodeling and heart dysfunction. Mammalian STE20-like kinase 1 (Mst1), a regulator of cellular apoptosis, is involved in cardiac remodeling in post-infarction heart, but the mechanisms remain poorly defined. We aimed to explore the role of Mst1 in regulating chronic post-infarction cardiac injury, with a focus on mitochondrial homoeostasis.MethodsWild-type (WT) and Mst1-knockout mice were as the cardiac myocardial infarction model. Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 60 publications
5
37
0
Order By: Relevance
“…At the histological and ultrastructural levels, the LVs of I/R hearts showed severe cardiomyocytes and mitochondria damage, thus confirming the important role of the mitochondria in I/R‐induced cardiomyocyte oxidative stress and apoptosis. All these data are supported by many other studies of different animal models with different I/R protocols 43‐45 …”
Section: Discussionsupporting
confidence: 70%
“…At the histological and ultrastructural levels, the LVs of I/R hearts showed severe cardiomyocytes and mitochondria damage, thus confirming the important role of the mitochondria in I/R‐induced cardiomyocyte oxidative stress and apoptosis. All these data are supported by many other studies of different animal models with different I/R protocols 43‐45 …”
Section: Discussionsupporting
confidence: 70%
“…Similarly, in a model of mouse diabetes, the AMPK pathway promotes the survival of tubular epithelium by correcting excessive mitochondrial fission. 51 With respect to the MAPK-JNK pathway, in-depth studies have uncovered the cross-talk between the MAPK-JNK axis and mitochondrial fission in models of liver cancer metastasis, post-infarction cardiac injury, 52 endometriosis, rectal cancer, 12 and microvascular ischemia–reperfusion insult. 21 In the present study, we found that Mst1 overexpression inactivated the AMPK-Sirt3 pathway, which was accompanied by an increase in mitochondrial fission.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we found that mitochondrial fragmentation could be repressed by MKP1 via inhibiting the JNK-CaMKII-Fis1 pathway. Actually, previous experiments have identified a causal relationship between JNK activation and excessive mitochondrial fission [18,61]. In addition, CaMKII phosphorylation has been proved to be the early event regulating the balance between mitochondrial fission and fusion [62].…”
Section: Discussionmentioning
confidence: 99%